Military land use and the impact on landscape: A study of land use history on Danish Defence sites. (May 2019) - Svenningsen, Stig Roar; Levin, Gregor; Perner, Mads Linnet
Highlights: Countrywide study of all larger defence sites in Denmark. An overall positive impact of military land use on land cover composition and biodiversity. A typology of six key LULC trajectories of Danish defence sites. Abstract: Counting for as much as 6% of Earth's terrestrial surface, military land use constitutes an important share of human land use. Yet, only few studies analyse the general impact of military land use on landscape and biodiversity. This article presents a countrywide study of land use, land use change and biodiversity content on all Danish defence sites larger than 10 ha, comprising roughly 40, 000 ha or 1% of the Danish terrestrial area. Based on interpretation of historical maps, land use history was analysed for the period from the 1870′s to the present. Furthermore, available national data were applied to assess present land use and biodiversity content within and in the surrounding of defence sites. The historical analysis revealed six typical trajectories of land use change. In terms of total area, the two most important were conservation of open, semi-natural habitat types (47%) and change from agriculture to open, semi-natural habitat types (34%). Results also show, that for sites characterised by these two land use change trajectories, present proportions of open semi-natural habitats as well as biodiversity contents are significantly higher within the sites compared to their surroundings. It is concluded that military land use in most cases had a significant beneficial impact on present day land cover composition and biodiversity.